Directors’ remuneration in listed small and medium scale firms: does corporate governance matter? - Ab Rashid, Hafiz Majdi; Annuar, Hairul Azlan; Anifowose, Mutalib (2019)
The study examines the relationship between corporate governance on directors’ remuneration of listed small and medium scale firms in Malaysia over the period of 2014 to 2017 on the 274 listed small and medium enterprises on the Bursa Malaysia. Six potential corporate governance mechanisms were utilised as surrogates which include Size, executive ownership, CEO duality, family relationship, independent non-executive directors on the remuneration committee, and board meetings and amount of remuneration package of all the directors was used as dependent variables. By controlling for potential endogeneity among the variables, the study estimates the data with system dynamic generalised method of moment. The result from this estimate reveals that five out of six corporate governance mechanisms significantly affect the directors’ remuneration among listed small and medium enterprises in Malaysia. The study concludes that CEO duality, board size, directors’ ownership, the presence of independent director on the remuneration committee and board meetings have a significant impact of directors’ remuneration among listed small and medium enterprises in Malaysia. Hence, the study recommends that the regulators should consider these factors in order tominimise the agency problem in this category of listed firms in the country. Though the findings from this study confirm the proposition upon which agency theory was developed, the scope of the studyis limited to small firms. Thus, the generalisation of the findings to large firms might not be feasible.